Testing the Efficiency of the Foreign Exchange Spot Market in Iran - Borhan-Azad, Lida (2006)
This dissertation aimed at testing the efficiency of the foreign exchange market of Iran in the weak and semi-strong form using data on the black market spot exchange rates between Iranian currency (i.e., Rial) and four major foreign currencies including US Dollar, German Mark/Euro, UK Pound and Japanese Yen. The weak form efficiency is examined by unit root tests including Augmented Dickey-Fuller (1979, 1981) (ADF) test and Phillips-Perron (1988) (PP) test. The results of these tests are consistent with the efficient market hypothesis theory indicating that the exchange rates are non-stationary and follow random walks. This supports the efficiency of the foreign exchange market of Iran in the weak form. However, the semi-strong form of efficiency is tested using tests of cointegration. These tests include the multiple cointegration methodology of Johansen (1991, 1995), Granger (1969) causality tests and variance decomposition analysis. The results of these tests provide evidence that there are long-term as well as short-term predictable relationships among the spot exchange rates. This is against the efficiency of the foreign exchange market of Iran in the semi-strong form. Furthermore, the evidence indicates that US Dollar has a significant role in the foreign exchange market of Iran. These results are meaningful for participants in the foreign exchange market and the government in Iran.